Komunikasi Secara Bi Al-Hikmah Dalam Al-Qur’an - Imam Dailami (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
The study of this study needs to be examined to understand the form or model of communication by using the bi-hikmah approach in the Qur‟an. The basic concept can be seen that, da‟wah communication in the perspective of the Qur‟an is almost the same as communication in general, but the difference between the two is only the way and objectives to be achieved. The purpose of communication in general is to expect participation from (mad'u) for ideas or messages that are conveyed by parties (da'i) so that the messages conveyed occur changes in attitudes and expected behavior, while the purpose of da'wah communication that is expecting the occurrence of changes or the formation of attitudes or behavior in accordance with the teachings of the Qur'an and hadith as sources of Islamic teachings. In the following case, it will explain about da'wah communication and its relationship with the Qur'an as the constitutional book of da'wah. It starts with the understanding of da'wah communication, the relationship between communication and da'wah, the characteristics of da'wah communication, the components of da‟wah communication, da'wah as persuasive communication and the ethics of communicating in the Qur'an. In other words the preaching of bi al-hikmah is a method of approach to da'wah communication carried out on a persuasive basis.